TINGKAT VOLATILITAS HARGA DAGING AYAM RAS DI JAWA TIMUR PADA BULAN RAMADHAN - Priyambodo, Ayu Wulandari; Rinanti, Rosyida Fajri (Universitas Tribhuwana Tunggadewi, 2024)
This study aimed to explore the impact of Ramadan on chicken meats in East Java. The ARCH/GARCH model is used in this study to assess whether or not beef has a price. Next, the GARCH model is used to analyze the effects of price volatility and fluctuations in Ramadan on the price of chicken meat in East Java. The ARCH-LM test's findings show that price volatility impacts changes in chicken meat prices. Then, the estimation results for the GARCH (1,1) model show that the volatility from the previous period and the variation in East Java from yesterday affect changes in chicken meat prices. GARCH (1,1) model displays.